Crystal structure, Hirshfeld surface, and DFT studies of 4-((pyrrolidin-1-ylsulfonyl)methyl)aniline - Krishnan, Soundararajan; Kaliyaperumal, Thanigaimani; Marimuthu, Ramalingam; Velusamy, Sethuraman (European Journal of Chemistry, 2021)
The crystal structure investigation of the title compound 4-((pyrrolidin-1-ylsulfonyl) methyl)aniline (PSMA) C11H16N2O2S shows that the molecule is essentially coplanar with a dihedral angle of 26.70(14)°between the pyrrolidine and the benzene rings. A pair of strong N-H···O hydrogen bonds produces continuous two-dimensional sheets with R22(18) ring motifs. The crystal structure also features a weak C-H···π interaction resulting in a three-dimensional network. Density functional theory (DFT) calculations reveal that the experimental and calculated geometric parameters of the molecule are nearly the same. Hirshfeld surface analysis has been carried out to study the various intermolecular interactions responsible for the crystal packing. Theoretical calculations indicate an excellent correlation between the experimental and the simulated UV spectra.